Knowledge sharing among hotel workers in Dubai, UAE. Issue 2 (3rd April 2022) - Newnham, Michael P.; Dutt, Christopher S.
Abstract: This paper explores knowledge sharing practices among hotel workers in Dubai. Results from a survey administered to 853 employees in five hotels suggested that there was little desire or initiative by employees to share knowledge, in contrast with most literature. Workers may use more knowledge seeking behavior. Support for this assertion stems from the distinctive composition of hotel workforces in Dubai, workers' employment circumstances, and their attitudes and motivation. Results suggest that employee performance might be enhanced if managers provide systems that support and encourage informal knowledge seeking in the workplace.